'Recuerdos del adolescente' (1922). Notas sobre un fragmento recuperado de "El juguete rabioso" - Corral, Rose (El Colegio de México, 2009)
This article reproduces and analyzes and unknown fragment of Roberto Artl’s first novel, El juguete rabioso (1926). Although this fragment, entitled “Recuerdos del adolescente”, published in 1922 in the literary magazine Babel (Buenos Aires), was discovered by Horacio Tarcus in 1997, it has not been reproduced in full until now. The text is an initial preview of a novel that is viewed as central to the Argentine literary tradition of the twentieth century. In 1922 the novel still had no title and the fragment was eliminated from the final version published by Arlt in 1926. As there are no manuscripts or early drafts of Arlt’s works, this text is important because it allows us to study an early stage of the novel’s elaboration.